The effect of Cooperative Learning Model Think-Talk-Write Type on Mathematical Problem-Solving Abilities In Terms of Learning Habits - Susanto, Agus Slamet; Bharata, Haninda; Dahlan, Syarifuddin (Al-Jabar: Jurnal Pendidikan Matematika, 2018)
The purpose of this research are: (1) to know the influence of Think Talk Write (TTW) model of learning ability to solve mathematical problems of learners; (2) to know the effect of learning habit on students' mathematical problem solving ability; (3) to know the interaction between learning model and study habit to students' mathematical problem solving ability. The type of research used is quasi experiment with 3 × 3 factorial research design. The hypothesis test used is a parametric test with data analysis technique using Anova test. The result of the research for the prerequisite test is based on normality test which can be known by using Liliefors test and homogeneity test can be known by using Barlett test, it is obtained that the test result data from both groups are normal and homogeneous, so it can be continued for parametric test by using anava test two paths with unequal cells. Based on data processing, it is found that: (1) there is influence of Think Talk Write (TTW) learning model to students' mathematical problem-solving ability; (2) there is the influence of learning habit on the ability of mathematical problem of learners; (3) there is no interaction between the learning model and the learning habits of the mathematical problems of the learners. This means that the learning model Think Talk Write (TTW) is more effective than the conventional model so that Think Talk Write (TTW) model more influence on the problem-solving ability of learners.